Correlation of pupil to limbus diameter ratio (pld ratio) with Blood pressure and pulse rate - ARUNA SAJEEVAN; KUMAR SAI SAILESH 1 (International Journal of Pharma and Bio Sciences, 2017)
The present study was undertaken to to assess the correlation between Pupil to Limbus Diameter (PLD) ratio with blood pressure and pulse rate. 50 apparently healthy working women were part of the study after obtaining written, voluntary, informed consent and ensuring confidentiality. All measurements were performed at 1 pm for the convenience of the participants and to overcome the effect of diurnal variation. Blood pressure and pulse rate was recorded from right hand. Pupil to Limbus Diameter (PLD) ratio was measured by two-box method as described in the literature. PLD ratio was measured at constant luminance for all the participants. Our study provides preliminary evidence for positive correlation of blood pressure and pulse rate with Pupil to Limbus Diameter (PLD) ratio. Further detailed studies with more autonomic parameters and with higher sample size are recommended for further evidence and to introduce measurement of Pupil to Limbus Diameter (PLD) ratio as a simple and convenient autonomic function test.